Update on the Mobilization of Loan Resources for PRGT Lending, Proposed Amendment to the PRGT Instrument, and Floor for the Six-Month Derived SDR Interest Rate. (Policy Papers; Policy Paper ;, 2016)
A Board-endorsed effort to raise SDR 11 billion in new Poverty Reduction and Growth Trust (PRGT) loan resources needed to sustain the Fund's concessional lending operations is well underway. Staff is now engaging with 16 interested loan providers bilaterally with a view to having firm pledges in line with the target by the 2016 Annual Meetings and a critical mass of new loan agreements in place by end-2016. To date, committed new loan resources amount to half of the SDR 11 billion fundraising target.